Evaluation method of the energy conversion efficiency of coal gasification and related applications. (13th November 2015) - Duan, Tianhong; Lu, Caiping; Xiong, Sheng; Fu, Zhenbing; Zhang, Bo
Summary: Traditional gasification parameters, such as cold gas efficiency, hot gas efficiency, or thermal efficiency, only evaluate the heat energy utilisation efficiency of gasifiers and do not take into account the gasification processes expending electricity and other types of energies. Therefore, the energy conversion efficiency cannot be assessed using these parameters. The calculation process on the energy conversion efficiency of underground coal gasification (UCG) is the basis for obtaining quantitative data of carbon emission reduction and establishing the carbon trading methodology of UCG. Moreover, the energy conversion efficiency both for surface coal gasification and UCG is a key research topic because it directly affects the economic and environmental benefits of gasification projects. This study proposed that two parameters, the integrated gasification efficiency ( h com ) and the hot gas integrated gasification efficiency ( h c o m ′ ), should be included into the coal gasification parameters and used to evaluate the energy conversion efficiency of coal gasification. In addition, the calculation methods of these two parameters for both surface gasification and UCG were established. Using the method, h com and h c o m ′, of the UCG and Texaco gasification under the same scale was compared and that of various UCG processes was calculated. The results proved the necessity and reasonability of the two parameters and suggested that a certain amount of CO2 was favourable to improve h com and h c o m ′ of UCG. However, a certain amount of pure O2 can improve h com of UCG without direct influences on h c o m ′ . Under the condition of each process, to maximise h com and h c o m ′, there must be an optimal steam (CO2 ) to O2 rate. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : The results prove the necessity and reasonability of h com and h c o m ′ proposed by this paper to evaluate the energy conversion efficiency of gasification processes. Calculated results suggested that a certain amount of CO2 was favourable to improve h com and h c o m ′ of UCG. Pure O2 in certain amount improves h com of UCG while showed no indirect influences on h c o m ′ . To maximize h com and h c o m ′, there must be an optimal steam (CO2 ) to O2 rate.